The perennials : the megatrends creating a postgenerational society - Guillén, Mauro F. (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2023)
"In today's world, the acceleration of megatrends--increasing longevity and the explosion of technology among many others--are transforming life as we now know it. In The Perennials, bestselling author of 2030 Mauro Guillén unpacks a sweeping societal shift triggered by demographic and technological transformation. Guillén argues that outmoded terms like Boomers, Gen X, Millennials, and Gen Z have long been used to pigeonhole us into rigid categories and life stages, artificially preventing people from reaching their full potential. A new postgenerational workforce known as "perennials"--individuals who are not pitted against each other either by their age or experience--makes it possible to liberate scores of people from the constraints of the sequential model of life and level the playing field so that everyone has a chance at living a rewarding life. Guillén unveils how this generational revolution will impact young people just entering the workforce as well as those who are living and working longer. This multigenerational revolution is already happening and Mauro Guillén identifies the specific cultural, organizational and policy changes that need to be made in order to switch to a new template and usher in a new era of innovation powered by the perennials"--